Assessing the economic profitability of Paulownia as a biomass crop in Southern Mediterranean area. (15th February 2022) - Testa, Riccardo; Schifani, Giorgio; Rizzo, Giuseppina; Migliore, Giuseppina
Abstract: The increase of renewable energy production worldwide, occurred in the last years, is also attributable to some agroforestry species cultivated according to the short rotation coppice technique. Although these species are able of enhancing abandoned or marginal land leading to numerous environmental benefits, an increasing number of farmers are introducing them in place of agricultural crops. Therefore, since for a farmer economic sustainability is one of the main factors to introduce a biomass crop, the study aimed at evaluating the profitability of Paulownia, a species that has been spreading in recent years. In particular, an economic analysis has been carried out in a Southern Italian farm in which Paulownia has recently replaced a vineyard, by adopting a discounted cash flow approach. The results show that the Paulownia for both timber and woodchip production, with an annual gross margin equal to 357.91 € ha −1, can represent a valid alternative compared to wine grape (237.41 € ha −1 ), while Paulownia for exclusively biomass production has almost zero profitability (4.22 € ha −1 ). However, the profitability depends not only on the product typology but also on the future market price fluctuations, on the subsidies or incentives, as well as on adequate choices by entrepreneurs for the creation of sustainable supply chains also from an environmental and social point of view. Graphical abstract: Image 1 Highlights: SRCs have denoted a rapid diffusion in the last years in UE also in Mediterranean area. SRCs are grown not only in abandoned or marginal land but also in place of traditional crops. Paper evaluates the economic profitability of SRC Paulownia in a southern Italian farm. Results show the higher profitability for Paulownia compared to wine grape. Market price variations and entrepreneurial choices affect profitability but also environmental and social sustainability.